Bad Influence of the Tretes Localization Area on the Mindset of the Young Generation in Pasuruan: Viewed from Social Learning Theory - Amalia, Ersa Nur; Nuriyah, Shinta; Azmiyah, Ulul; Kholifah, Nanik (World Psychology, 2024)
The Tretes localization area is an area where prostitution activities grow and develop. Prostitution activities in the Tretes localization area greatly affect the community, especially the younger generation in Pasuruan. This research aims to examine and find out how much influence the Tretes localization area has on the mindset, psychology and lifestyle of the young generation in Pasuruan, in terms of social learning theory. This research is qualitative descriptive research with the research participant of the younger generation in Pasuruan and the object is to focus on how much bad influence the Tretes localization area has, which is more dominant, on aspects of thought patterns, psychology or lifestyle in the younger generation in Pasuruan. The results of this research show that the aspect of the mindset of the younger generation in Pasuruan is the aspect that is most dominantly affected by the bad influence of the Tretes localization area.